Optimism and Activism: Establishing the Confucian Way Through Renxing - Sigurdsson, Geir (Acta Orientalia Vilnensia, 2004)
In recent years, there has been considerable controversy over the notion of xing as it appears in the Mencius and in the Xunzi. The controversy has mostly revolved around the questions whether xing refers to a universal human nature or not, and whether their notions of shan and e can be accurately characterized as ‘good’ and ‘evil’. In this paper, the issue will be approached differently, and the issue of xing’s universal or non-universal scope largely ignored as unproductive. Instead, it will be argued that a more productive approach is to view Mencius’ and Xunzi’s differing claims about the quality of xing of human beings as reflecting their different practical considerations of how best to establish the Confucian way. The Mencian emphasis, then, on the goodness of human beings is an attempt to resist cynicism and defeatism in a time in which wars and horrors were common, and to maintain a belief in the possibility of realizing a harmonious and peaceful society: Mencius underscores the optimistic spirit in the philosophy initiated by Confucius. On the other hand, Xunzi’s claim about the problematic or unruly tendencies in the human xing are possibly resistances to a kind of thinking that celebrates passive conformity to natural processes: Xunzi emphasizes the active element in Confucius’ thought. Optimism and activism are both integral features of the Confucian spirit. Hence it is misleading to regard Mencius and Xunzi as contradicting each other in their divergent claims about xing. Since their claims rather rest on different practical considerations, they merely emphasise different aspects of Confucius’ thought, and, taken together, rather complement each other.